Influence of temperature and extraction time on gel strength and yield of gelatin from speckled smooth-hound skin (Mustelus mento) - Miano, Alberto (2014)
In the present study was determined the parameters of temperature and extraction time to achieve higher yield and gel strength of gelatin from speckled smooth-hound skin (Mustelus mento) by alkaline hydrolysis. It was used the central composite rotational design (CCRD) with 11 experiments with temperatures between 60ºC and 95°C and extraction time between 30 minutes and 240 min. It was concluded that with higher extraction times, higher yield percentage will get, and with lower extraction temperature, higher gel strength will get. For obtaining higher yield (27% – 28%) and greater gelatin gel strength (130 - 150g Bloom), we used 220 and 240 minutes, and temperatures between 60 and 65 °C.